Testing the Transportation-induced Environmental Kuznets Curve Hypothesis: Evidence from Eight Developed and Developing Countries - Ozkan, Turgut; Yanginlar, Gozde; Kalayci, Salih (International Journal of Energy Economics and Policy, 2018)
This paper focuses on the relationship between air transportation, economic growth, and carbon emissions in 8 developing and 8 developed countries during the period 1980–2013 by testing the Environmental Kuznets Curve hypothesis. We use annual panel data from the World Bank in order to demonstrate environmental sensibility of both developed and developing countries. In this context, the research results demonstrate that environmental sensitivity is pretty low for both developed and developing countries in the period 1980-2000. Afterwards, the environmental issues of the two groups of countries are evaluated over the period from 2001 to 2013 and the research results indicate that their sensitiveness has increased remarkably, which supports the inverse-U shape of the Environmental Kuznets Curve. These empirical results are also consistent with the Kyoto protocol’s political aims and goals. In addition, based on the Johansen co-integration test results, there is a long-term stable relationship between as air transportation, CO2 emissions, energy use, and GDP for both developed and developing countries, with the exception of Colombia and Turkey. Keywords: Transportation, EKC hypothesis, International economics JEL Classifications: L91, Q50, F10 DOI: https://doi.org/10.32479/ijeep.7330